Application of the high-frequency base balance technique to tall slender structures considering the effects of higher modes. (15th November 2017) - Zou, Lianghao; Shi, Tianyi; Song, Jie; Cai, C.S.
Highlights: A novel HFBB analysis approach that considers the effect of higher modes has been developed. The accuracy of the proposed method was validated for three typical lattice towers. The proposed method exhibits a significant advantage for estimating wind-induced responses, especially for the TV tower. The proposed method greatly extends the application of the HFBB technique to slender structures. Abstract: This paper presents a novel high-frequency base balance (HFBB) analysis approach that considers the effect of higher modes on wind-induced responses of tall slender structures. The generalized force for any mode is formulated by assuming a distribution of the wind force power spectral density (PSD) along the structural height, and employing the base moments measured from HFBB wind tunnel tests. The structural responses are then calculated by solving the equation of motion. The accuracy of the proposed method is validated by comparing the results from the proposed method with those from associated aeroelastic model testing, for a microwave communication tower, an electrical transmission tower and a TV tower. The results show that the proposed method exhibits a significant advantage for estimating wind-induced responses, especially for the TV tower. This is because the proposed method takes account of the contribution of the higher modes, which are usually not ignorable for tall and flexible lattice towers. Therefore, the proposed method greatly extends the application of the HFBB technique to tall and flexible structures where the effects of higher modes are significant.